2005
DOI: 10.1590/s0100-40422005000500010
|View full text |Cite
|
Sign up to set email alerts
|

O impacto industrial na composição química das águas subterrâneas com enfoque de consumo humano (Rio Grande, RS)

Abstract: In 70-85% of the studied area, fluoride, nitrate and phosphate in groundwater surpass the maximum limits for human consumption according to Brazilian environmental legislation. The chemical spectrum of contaminants and their spatial distribution show that fertilizer production processes are responsible for groundwater pollution. The natural conditions of the region are not favorable for minimal protection against infiltration of pollutants into the aquifer.Keywords: groundwater; industries; pollution. INTRODUÇ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
11

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 3 publications
2
6
0
11
Order By: Relevance
“…Esses são os maiores problemas de contaminação dos recursos hídricos em regiões rurais [5]. A situação torna-se potencialmente grave quando esta água contaminada é destinada ao consumo humano.…”
Section: Introductionunclassified
“…Esses são os maiores problemas de contaminação dos recursos hídricos em regiões rurais [5]. A situação torna-se potencialmente grave quando esta água contaminada é destinada ao consumo humano.…”
Section: Introductionunclassified
“…Research conducted in Rio Grande has found high concentrations of pollutants, including metals such as lead, mercury, arsenic and HPAs (aromatic polycyclic hydrocarbons) in different environmental compartments, such as in air, water, soil and sediment [8][9][10]41]. The effects of these pollutants on children's intellectual functioning are well known.…”
Section: Discussionmentioning
confidence: 99%
“…A delimitação da área de influência de poços e a identificação das classes de uso da terra foram feitas utilizando- Vários autores têm relatado a contaminação da água subterrânea como consequência do uso da terra (CHAE et al, 2004;DAS et al, 2010;MIRLEAN et al, 2005;CALIJURI et al, 2012;LI;MERCHANT, 2013;STROHSCHÖN et al, 2013;WHITE et al, 2013). Os impactos do uso da terra sobre a qualidade da água subterrânea incluem: aumento das concentrações de íons, mudanças nas condições de óxido-redução e aumento das concentrações de elementos secundá-rios nas regiões em desenvolvimento em comparação com regiões não desenvolvidas (TROJAN et al, 2003).…”
Section: Introductionunclassified